2020
DOI: 10.3390/agronomy10122018
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Structure and Photosynthetic Performance of Irrigated Cassava Genotypes Growing in Different Seasons in a Tropical Savanna Climate

Abstract: Growth and photosynthesis performance of cassava during early vegetative growth are important determinants of final biomass. The objective of this work was to investigate canopy structure and photosynthesis performance of four cassava genotypes (Rayong 9, Rayong 11, Kasetsart 50, and CMR38-125-77) growing under irrigation at 3 and 6 months after planting (3MAP and 6MAP). Data for the 3MAP plants were collected from cassava planted on 30 June (Rainy PD), 10 November (Cool PD1), and 15 December (Cool PD2) 2015; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
2
5
1
Order By: Relevance
“…The response of leaves in the upper layer, which has high photosynthetic activity, to light intensity was compared with previous reports. While the A max in this study was 21.3-25.1 µmol m −2 s −1 , Santanoo et al [18] and Mahakosee et al [19] reported it to be approximately 30 µmol m −2 s −1 . PAR at a light saturation of A was also reported to be about 1500 µmol m −2 s −1 , higher than the 1200 µmol m −2 s −1 reported in this study.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The response of leaves in the upper layer, which has high photosynthetic activity, to light intensity was compared with previous reports. While the A max in this study was 21.3-25.1 µmol m −2 s −1 , Santanoo et al [18] and Mahakosee et al [19] reported it to be approximately 30 µmol m −2 s −1 . PAR at a light saturation of A was also reported to be about 1500 µmol m −2 s −1 , higher than the 1200 µmol m −2 s −1 reported in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…PAR at a light saturation of A was also reported to be about 1500 µmol m −2 s −1 , higher than the 1200 µmol m −2 s −1 reported in this study. One of the reasons for this is that Kagoshima, where this experiment was conducted, is at a higher latitude and receives less solar radiation than Khon Kaen, Thailand, where Santanoo et al [18] conducted their experiments. The result of light curve on different canopy height levels showed high A max on the upper layer and photosynthesis was conducted under high solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was observed that P N of HN and KU50 varied across the developmental stages, exhibiting a V-shaped pattern ( Figure 1A ). This pattern was also observed in other cassava varieties, including Rayong 9 ( Vongcharoen et al, 2018 ; Santanoo et al, 2020 ), Rayong 11, CMR38-125-77 ( Santanoo et al, 2020 ), MBra 110, MMal 48, MCol 22, and MPan 51 ( El-Sharkawy and De Tafur, 2010 ), indicating a characteristic of cassava species. The results indicate a strong interconnection between photosynthesis capacity and intracellular carbon metabolism and allocation.…”
Section: Discussionsupporting
confidence: 59%
“…Phoncharoen et al [44] also reported that the genotype Rayong 9 had high values of storage root yield and harvest index due to its high capability of partitioning photosynthates to sink. Santanoo et al [45] indicated that the genotype Rayong 9 grown under irrigated conditions had a high net photosynthesis rate. The positive correlation between leaf net photosynthetic rate and storage root yield has been reported by El-Sharkawy [46,47].…”
Section: Performances Of the Four Cassava Genotypesmentioning
confidence: 99%